Faktor-Faktor yang Mempengaruhi Pemilihan Karir Akuntan Publik dan Non Akuntan Publik - Merdekawati, Dian Putri; Sulistyawati, Ardiani Ika (Jurnal Ilmu Ekonomi ASET, 2011)
The purpose of this study was to determine whether there was influencethe selection of a career as a public accounting, corporate accountant, accountants,educators, and government accountants of the factors that will be reviewed financialawards, professional training, professional recognition, social values , work environment,labor market considerations and personality. The population in this study were active S1Accounting students at 6 private universiies in Semarang city on six semesters as manyas 200 students. The sample selection was done by using random sampling, the resultingsample of 125 respondents consisting of 35 students of UNISSULA, 35 students of UNIKA,35 of USM students, 35 students of UDINUS, 35 students of UNISBANK, and 25 studentsof WIDYA Manggala School of Economics. The data analysis was conducted in thisstudy by using ANOVA test. The results of this study indicate that there was influence inthe choice of accounting students as a career public accountant, company accountant,accounting educators, and government accountants who reviewed the factors of financialreward, professional training, professional recognition, social values , work environment,labor market considerations and personality.Keywords: financial rewards, professional training, professional recognition, socialvalues â , work environment, labor market considerations, personnel